OpenSHMEM and related technologies : big compute and big data convergence : 4th Workshop, OpenSHMEM 2017, Annapolis, MD, USA, August 7-9, 2017, Revised selected papers /: big compute and big data convergence : 4th Workshop, OpenSHMEM 2017, Annapolis, MD, USA, August 7-9, 2017, Revised selected papers. ([2018]) - Unknown
No abstract available